Age based mechanics of maximal jump performance in endurance athletes - Diss, C.; Gittoes, M.; Tong, R.; Kerwin, D. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to explore age based maximal jump performance responses, and the underlying kinetic contributions of endurance athletes. Master athletes (aged 60 to 68 years) jumped significantly lower than the younger athletes (aged 26 to 32 years), which was evidenced by a lower vertical velocity at take off by 0.79 m·s-1. The significant positive correlation of lower body stiffness with age was mainly attributed to increased knee stiffness from 0.54 to 1.43 x 10-2 (o-1) for the younger to the master athletes, respectively. Exploring the knee moment associated with joint stiffness revealed that the change in knee moment in the eccentric phase was comparable between the groups and was not correlated with age. Therefore, the increased knee stiffness with age may be attributed to the restricted knee flexion in the eccentric phase.